PELAKSANAAN PERLINDUNGAN HUKUM BAGI DEBITUR DALAM PERJANJIAN KREDIT PERSPEKTIF UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (Studi pada Bank Perkreditan Rakyat (BPR) Tri Hasta Prasojodi Jaten Karanganyar) - Hartanto, Harris Budi; , Septarina Budiwati S.H., M.H; , Shallman Al Farizi, S.H., M.H., M.Kn (2015)
Bank credit agreement is a preliminary agreement on the delivery of money. Bank credit agreement generally use the standart contract form, in pratice agreement from has been provided by the bank as creditors while the debtor is only in a posistion to accept or reject without any possibility for negotiation or bargaining, which in turn gave brith to a treaty that is not very favorable to one party. In such agreements, the second party (the debtor) is simply not able to propose or input and objections to the format of agreements and clauses in it. This study uses empirical juridical descriptive analytical. By using the primary data and secondary data. Data collection techniques using literature study and interview method. By using the method of data analysis qualitative analysis. Based on the result of research and discussion, it can be concluded that the clause contained in the credit agreement No. 969/XXII/06/SR/2014 dated June 3, 2014 there are some clauses that ulltimately "not too favorble" to the debtor. In accordance with the provisions of article 18 of custommer protection act so that the debtor deserve legal protection. Clauses contained in the loan agreement No. 969/XXII/06/SR/2014 dated June 3, 2014 which has been in accordance with the provision of article 18 paragraph (1) letter a and g. Keyword: Credit agreement, Legal Protection For Debtor, Confornity Clause Credit Agreement With Customer Protection Act.